Leverage - Santos, Tano; Veronesi, Pietro (Journal of Financial Economics, 2022)
A frictionless general equilibrium model featuring heterogeneous time-varying risk tolerance explains the business cycle dynamics of intermediary leverage, aggregate credit, and other asset markets’ facts. In booms, when risk tolerance is high, households borrow more and aggregate credit increases funded by higher intermediary debt. In recessions, credit contracts and intermediaries delever. Yet, their debt-to-equity ratios increase as equity drops when risk aversion increases. Because households borrow more or less as their risk tolerance increases or decreases, the intermediary’s balance sheet forecasts stock returns both in the time series and the cross section. Moreover, credit expansions correlate with negatively skewed stock returns, low credit spreads, and predict lower future returns.